Evaluación de diferentes niveles de inclusión de pulpa de café biofermentada en raciones para cuyes durante la fase de crecimiento-engorde en la ciudad de Loja - Calderón Aguirre, Santiago Efraín (2015)
This research was conducted at the breeding farm “D.A.S” located in Loja canton, in “Carigán” neighborhood with the purpose of evaluating the different inclusion levels of bio-fermented coffee pulp in portions of food for guinea pigs during the growth-fattening process. The study was made in 16 weeks, in which the first 4 weeks the bio-fermentation process was performed using ensiled coffee pulp and preparation of food portions by mixing the pulp with other ingredients such as: corn meal, alfalfa meal, soybean meal, wheat bran and pecutrin; adjusting the percentage of protein per serving to 17 %. During the next twelve weeks there were used 60 male weaned guinea pigs, which were distributed in four treatments, each one of 15 animals divided into three replicates of 5 animals. The witness portion T1 doesn´t include coffee pulp but the following portions included coffee pulp: T2 (15 %), T3 (25%) and T4 (35%). Feeding was exclusively based on concentrate, water and vitamin C. The following objectives were established: to determine weight gain, feed conversion , and the profitability of the guinea pigs in growth- stage of fattening subjected to different treatments; to determine the ideal concentration of bio fermented coffee pulp as a nutritional supplement in the feeding of guinea pigs ; to evaluate the profitability of using bio fermented coffee pulp as part of guinea pig diet . The results showed that the greatest weight was reached with the T1 treatment (904 g), and the lowest in T4 treatment (883 g). These weights are consistent with the initial weight of each treatment: T1 was higher (379 g) T4 (354 g). The greatest profitability increased in weight was obtained with T2 treatment (548 g) and with the T4 treatment (528 g) as well as it was obtained a better feed conversion in the same order: T2 (7.97) and T4 (8.19). Mortality was 6.67% in T1, T2 and T4 groups. The highest profitability was obtained in T4 (8.07 %.) With the results obtained it was proved the profit of including ensiled coffee pulp bio fermented in the preparation of guinea pigs food portions. Keywords: Coffee pulp, grow-finish, weight gain, feed conversion, mortality, return.